Functionalized Metal‐Supported Reversible Protonic Ceramic Cells with Exceptional Performance and Durability. Issue 2 (2nd December 2021) - Wang, Yuhao; Song, Yufei; Liu, Jiapeng; Yang, Kaichuang; Lin, Xidong; Yang, Zhibin; Ciucci, Francesco
Abstract : Reversible protonic ceramic cells (RePCCs) are limited by several factors, including high cost, poor stability, and insufficient fuel electrode activity toward fuel oxidization/generation reactions. Herein, a novel Ni−Fe metal‐supported RePCC (MS‐RePCC) to address these issues simultaneously is proposed. Specifically, the Ni−Fe support possesses good mechanical strength and thermal compatibility with cermet‐based electrodes/electrolytes, ensuring a facile cell fabrication and robust durability. Density functional theory calculations suggest that Fe in the Ni−Fe support enhances the fuel electrode functional layer by providing additional and more active sites for the electrocatalytic reactions. The as‐fabricated MS‐RePCC at 700 °C achieves an excellent peak power density (PPD) of 586 mW cm −2 and an electrolysis current of −428 mA cm −2 (at 1.3 V). Furthermore, the cell is exceptionally stable, as evidenced by 930 h of fuel cell operation with ultralow degradation (≈0.78% kh −1 ), and much better than an analogous anode‐supported cell (≈17.78% kh −1 ). In addition, the cell is stable for 50 h of reversible fuel cell/electrolyzer cycling, further demonstrating the potential of this MS‐RePCC. This article proposes a simple and new approach to enhance the electrochemical activity and durability of RePCC, thereby accelerating the commercialization of this technology. Abstract : A Ni−Fe metal‐supported reversible protonic ceramic cell is developed. The alloy support has excellent thermal compatibility with other components of the cell. Further, it promotes the electrocatalytic activity of the fuel electrode. The prepared device shows ultrahigh stability during both fuel cell and electrolysis operation.